2004
DOI: 10.4319/lom.2004.2.282
|View full text |Cite
|
Sign up to set email alerts
|

The Bunsen gas solubility coefficient of ethylene as a function of temperature and salinity and its importance for nitrogen fixation assays

Abstract: The acetylene reduction assay is a common method for assessing nitrogen fixation in a variety of marine and freshwater systems. The method measures ethylene, the product of the conversion of the gas acetylene to its reduced form by nitrogenase. Knowledge of the solubility of ethylene in aqueous solution is crucial to the calculation of nitrogen fixation rates and depends on the temperature and salinity of the assay conditions. Despite the increasing interest in marine nitrogen fixation, no gas solubility (Buns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 21 publications
0
69
0
Order By: Relevance
“…Nitrogenase activity was measured through the reduction of acetylene to ethylene (acetylene reduction assay, ARA) (Hardy et al 1968). By incubating the GF/F filters we were able to use the sensitive ARA on large water volumes without running into experimental problems due to high gas volume : water volume ratios (Breitbarth et al 2004). Previously, we demonstrated that the measurement of nitrogenase activity by incubation of biomass on filters is preferred over incubation in suspension because of the slow diffusion of gasses (Staal et al 2001 Incubations lasted 10-12 h. The gas phase of the vials was sampled with a 500-mL gastight syringe (Hamilton) and manually injected into a gas chromatograph (GC14A, Shimadzu) equipped with a flame ionization detector (FID) (Staal et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogenase activity was measured through the reduction of acetylene to ethylene (acetylene reduction assay, ARA) (Hardy et al 1968). By incubating the GF/F filters we were able to use the sensitive ARA on large water volumes without running into experimental problems due to high gas volume : water volume ratios (Breitbarth et al 2004). Previously, we demonstrated that the measurement of nitrogenase activity by incubation of biomass on filters is preferred over incubation in suspension because of the slow diffusion of gasses (Staal et al 2001 Incubations lasted 10-12 h. The gas phase of the vials was sampled with a 500-mL gastight syringe (Hamilton) and manually injected into a gas chromatograph (GC14A, Shimadzu) equipped with a flame ionization detector (FID) (Staal et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Subsamples of the headspace were removed immediately after the injection of acetylene and at the end of the incubation, and ethylene was analyzed by a flame ionization gas chromatograph (GC-17A, Shimadzu). Then, the ethylene production during the incubation was calculated after Breitbarth et al (2004). The produced ethylene was converted to fixed nitrogen with a molar ratio of 4 : 1.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were gently agitated to equilibrate gas concentrations between the headspace and culture samples after injecting acetylene and before measuring ethylene concentrations. We used a Bunsen coefficient for ethylene of 0.082 (Breitbarth et al 2004) and an ethylene production : N 2 fixation rate ratio of 3 : 1, and we calculated N 2 -fixation rates over 14 h (this included the 12 h dark cycle and the first 2 h of the light cycle).…”
Section: Methodsmentioning
confidence: 99%